Vonoprazan versus conventional proton pump inhibitor‐based triple therapy as first‐line treatment against Helicobacter pylori: A multicenter retrospective study in clinical practice. Issue 10 (October 2016) - Shichijo, Satoki; Hirata, Yoshihiro; Niikura, Ryota; Hayakawa, Yoku; Yamada, Atsuo; Mochizuki, Satoshi; Matsuo, Keigo; Isomura, Yoshihiro; Seto, Motoko; Suzuki, Nobumi; Suzuki, Hirobumi; Yamamoto, Shinzo; et al.
Abstract: Objective: Vonoprazan is a potassium‐competitive acid blocker, a new type of acid‐suppressing drug, and has recently become available for peptic ulcers, gastroesophageal reflux disease, and Helicobacter pylori ( H. pylori ) eradication. Its efficacy for H . pylori eradication has been reported. However, the evidence for its efficacy and feasibility remains limited. We aimed to compare the feasibility, effectiveness and safety of vonoprazan‐based triple therapy with conventional proton pump inhibitor (PPI)‐based triple therapy in multicenter clinical practice. Methods: We performed a multicenter retrospective study on patients receiving first‐line H . pylori eradication therapy between March 2013 and November 2015 with either vonoprazan‐based triple therapy or conventional PPI‐based triple therapy. Results: A total of 2715 patients aged 63.0 ± 12.1 years (1412 [52.0%] males) were analyzed. Eradication rates were 87.2% (368/422) for vonoprazan‐based therapy and 72.4% (1661/2293) for conventional PPI‐based therapy ( P < 0.01). Among the former group, there were 10 cases of diarrhea, six of nausea/vomiting, and five of rash, but the rates of these adverse events were similar to those in the conventional PPI group. Conclusion: Vonoprazan‐based triple therapy is feasible, and has a higher rate for H. pylori eradication than conventional PPI as a first‐line regimen.